Percutaneous Epicardial Pacing using a Novel Insulated Multi-electrode Lead - Syed, Faisal F; DeSimone, Christopher V; Ebrille, Elisa; Gaba, Prakriti; Ladewig, Dorothy J; Mikell, Susan B; Suddendorf, Scott H; Gilles, Emily J; Danielsen, Andrew J; Lukášová, Markéta; Wolf, Jiří; Leinveber, Pavel; et al. (JACC. Clinical electrophysiology, 2015)
INTRODUCTION: Epicardial cardiac resynchronization therapy (CRT) permits unrestricted electrode positioning. However, this requires surgical placement of device leads and the risk of unwanted phrenic nerve stimulation. We hypothesized that shielded electrodes can capture myocardium without extracardiac stimulation. METHODS: In 6 dog and 5 swine experiments, we used a percutaneous approach to access the epicardial surface of the heart, and deploy novel leads housing multiple electrodes with selective insulation. Bipolar pacing thresholds at prespecified sites were tested compare electrode threshold data both facing towards and away from the epicardial surface. RESULTS: In 151 paired electrode recordings (70 in 6 dogs; 81 in 5 swine), thresholds facing myocardium were lower than facing away (median [IQR] mA: dogs 0.9 [0.4-1.6] vs 4.6 [2.1 to >10], p<0.0001; swine 0.5 [0.2-1] vs 2.5 [0.5-6.8], p<0.0001). Myocardial capture was feasible without extracardiac stimulation at all tested sites, with mean ± SE threshold margin 3.6±0.7 mA at sites of high output extracardiac stimulation (p=0.004). CONCLUSION: Selective electrode insulation confers directional pacing to a multielectrode epicardial pacing lead. This device has the potential for a novel percutaneous epicardial resynchronization therapy that permits placement at an optimal pacing site, irrespective of the anatomy of the coronary veins or phrenic nerves.
Keywords: multisite pacing; epicardial mapping; cardiac resynchronization therapy; epicardial pacing; phrenic nerve stimulation; Biventricular pacing; steerable pericardial sheath; minimally invasive; pericardial intervention; bioelectrical therapy